Religion and Belief in Indonesia’s Education System: Constitutional Recognition Amid Institutional Marginalization - Nenohai, Jear Niklas Doming Karniatu (Journal of Contemporary Sociological Issues, 2025)
Changes in Indonesia's educational framework consistently align with shifts in the governing administration. Each variation of these reforms reveals a recurring pattern: Indigenous religious groups, holding minority status, regularly face discrimination due to these policies. Unfortunately, recognizing the indigenous belief system in education as a legitimate form of instruction within Indonesia remains elusive. The primary driver of this discriminatory practice is rooted in the principles of the belief system in education, currently regulated by the guidelines of the Ministry of Education and Culture (KEMENDIKBUD). Critics widely believe that this belief system symbolizes exclusion, deviating from inclusivity and misaligning with the fundamental principles outlined in the 1945 Constitution. Previous scholars have convincingly argued that the marginalization of Indigenous education directly stems from orchestrated religious politics. The prejudicial treatment extends beyond the dominance of world religions and is fundamentally based on religious exclusion. This exclusionary practice involves transforming Indigenous education into a secular and anthropocentric framework. A clear example of this exclusion is visible in the intentional separation of religious education from its indigenous counterpart. This is evident in the current administration, where the Ministry of Education and Culture oversees indigenous education, while the Ministry of Religion recognizes only six religions. Within the existing state paradigm, indigenous education is confined to secularism, stripped of its religious character. Given this reality, this paper argues that marginalization continuously occurs within the context of Indonesia’s educational system. Keywords: Belief, Education, Freedom, Indigenous, Religious